Entertainment Authority Mobile Application Saudi Arabia: Smart Station - Khairallah, Enas (Journal of King Abdulaziz University: Computing and Information Technology Sciences, 2023)
Bus service is considered as one of the major public transportations used by the people. Especially in the areas that have many people such as festivals. Nowadays, there are many events and festivals are going on in Jeddah city. Moreover, there is a huge need to the bus services during the Jeddah season. At the same time, this service has many difficulties faced visitors and bus drivers, such as: lack of information about the bus (location of a bus in real-time, status of a bus: empty or full), and lack of information about the bus stations. Moreover, and based on real experiment during Jeddah’s season waiting in the bus station is a frustrating process. Therefore, this paper proposed a mobile application on google play that facilitates the transportation between the event’s areas by seeing the bus location map and the number of empty passenger seats. The application also serves the bus driver, by clarifying if there is someone at the bus station or not so the driver can decide to move to the next station or stop in the station. A sensor device and LCD screen are used to help in the counting process. There are many goals of the proposed project the main goal is to make an application that serves a large segment of society during the festival seasons of the Saudi Entertainment Authority especially in transportation: i) organizes and facilitates transportation in the Jeddah season for entertainment, ii) save visitor’s time and reduce traffic by tracking the bus location, knowing distance between the user and bus, and the number of bus passengers, and iii) easy and simple user interface for easy use. To evaluate the proposed application many tests and evaluation tools have been used and prove the effectiveness of the application.